Chromosome 9p21.3 is Associated with Early-Onset Coronary Heart Disease in the Irish Population. Issue 2 (4th June 2013) - Meng, Weihua; Hughes, Anne E.; Patterson, Chris C.; Belton, Christine; Kee, Frank; McKeown, Pascal P.
Abstract : Coronary heart disease (CHD) remains a leading cause of death across the world. A region on chromosome 9p21.3 has been recently reported to be associated with CHD. We evaluated 3 SNPs and 3 common haplotypes in the 9p21.3 region in 1494 individuals from 580 Irish families, where at least 1 member had early-onset (males ≤55yr, females ≤60yr) CHD. Genotypes were determined by multiplex SNaPshot technology. Using the combined TDT/S-TDT test, the 3 single nucleotide polymorphisms (SNP), rs10757274, rs2383206 and rs1333049, were strongly associated with early-onset CHD ( p = 2.7 × 10 -6, 2.7 × 10 -6, 3.8 × 10 -7, respectively). Analysis of haplotypes by the TRANSMIT program also showed that the GGC haplotype was associated with early-onset CHD ( p = 7.9 × 10 -7 ). In conclusion, using a family-based approach in the Irish population, we have confirmed previous reports of association between a region on chromosome 9p21.3 and early-onset CHD.